(untitled) (Gaceta Técnica, 2018)
This research presents the behavior of a real scale experimental column-beam joint formed by three reinforced concrete elements, 1 column and 2 beams, attached to a structural steel column in the upper level is studied. The specimen in question was subjected to the action of cyclic loads in a single direction, in a pseudostatic test for 5000 s, in order to observe which element of the specimen failed and which the failure mode was. The investigation was based on the use of digital images taken throughout the test, during the loading and unloading cycles, each photo being analyzed with the CORRELI-Q4 subroutine, in order to visualize the places where cracking occurs in the concrete. The use of the application allowed to reveal how cracking in the reinforced concrete occurred during the test, and that the column of reinforced concrete was the one that was most affected by cracking, with cracks just below the concrete beams.